Mdm2‐p53‐SF1 pathway in ovarian granulosa cells directs ovulation and fertilization by conditioning oocyte quality. Issue 2 (27th September 2018) - Haraguchi, Hirofumi; Hirota, Yasushi; Saito-Fujita, Tomoko; Tanaka, Tomoki; Shimizu-Hirota, Ryoko; Harada, Miyuki; Akaeda, Shun; Hiraoka, Takehiro; Matsuo, Mitsunori; Matsumoto, Leona; Hirata, Tetsuya; Koga, Kaori; et al.
ABSTRACT: Functions of tumor suppressor p53 and its negative regulator mouse double minute 2 homolog (Mdm2) in ovarian granulosa cells remain to be elucidated, and the current study aims at clarifying this issue. Mice with Mdm2 deficiency in ovarian granulosa cells [ Mdm2‐l oxP /progesterone receptor ( Pgr )‐Cre mice] were infertile as a result of impairment of oocyte maturation, ovulation, and fertilization, and those with Mdm2/p53 double deletion in granulosa cells ( Mdm2 ‐loxP/ p53 ‐loxP/ Pgr ‐Cre mice) showed normal fertility, suggesting that p53 induction in the ovarian granulosa cells is detrimental to ovarian function by disturbing oocyte quality. Another model of Mdm2 deletion in ovarian granulosa cells ( Mdm2‐ loxP /anti‐Mullerian hormone type 2 receptor‐ Cre mice) also showed subfertility as a result of the failure of ovulation and fertilization, indicating critical roles of ovarian Mdm2 in ovulation and fertilization. Mdm2‐p53 pathway in cumulus granulosa cells transcriptionally controlled an orphan nuclear receptor steroidogenic factor 1 (SF1), a key regulator of ovarian function. Importantly, MDM2 and SF1 levels in human cumulus granulosa cells were positively associated with the outcome of oocyte maturation and fertilization in patients undergoing infertility treatment. These findings suggest that the Mdm2‐p53‐SF1 axis in ovarian cumulus granulosa cells directs ovarian function by affecting their neighboring oocyte quality.—Haraguchi, H., Hirota, Y., Saito‐Fujita, T., Tanaka, T., Shimizu‐Hirota, R., Harada, M., Akaeda, S., Hiraoka, T., Matsuo, M., Matsumoto, L., Hirata, T., Koga, K., Wada‐Hiraike, O., Fujii, T., Osuga, Y. Mdm2‐p53‐SF1 pathway in ovarian granulosa cells directs ovulation and fertilization by conditioning oocyte quality. FASEB J. 33, 2610–2620 (2019). www.fasebj.org